Clinicopathological Characteristics and Survival Outcomes of Primary Renal Leiomyosarcoma - Chen, Cheng; Jiang, Xinjie; Xia, Fei; Chen, Xudong; Wang, Weiguo (Frontiers in Surgery, 2021)
Background: Primary renal leiomyosarcoma (LMS) is exceedingly rare entity with poor prognosis. Here, we summarized its clinicopathological characteristics, treatment choice and survival outcomes using the Surveillance, Epidemiology, and End Results (SEER) database. Methods: All the data of renal LMS and renal clear cell carcinoma (KIRC) from 1998 to 2016 was collected from the SEER database. For continuous variables, t-test was used. For categorical variables, Pearson’s Chi-squared or Fisher exact test was used. Propensity score matching (PSM) was conducted. Cancer specific survival (CSS) and overall survival (OS) curves were estimated by the Kaplan-Meier analyses and compared by the log-rank test. The risk factors on CSS and OS was estimated by the univariable and multivariable Cox proportional hazard regression model. Results: In total, 140 patients of renal LMS and 75401 patients of KIRC were finally collected. There were significant differences in sex, race, tumor size, grade, SEER stage, patients receiving surgery, radiation and chemotherapy between renal LMS and KIRC. Renal LMS exhibited poor CSS and OS compared with KIRC before and after PSM. For renal LMS, univariate Cox proportional hazard regression model indicated that larger tumor size, higher tumor grade, higher SEER stage and receiving chemotherapy were risk factors for CSS and OS. Patients receiving surgery was a protective factor. However, only tumor grade, SEER stage and receiving surgery remained independent prognostic factors in multivariable Cox proportional hazard regression model. In addition, subgroup analyses indicated that patients receiving surgery remained protective factor for advanced renal LMS. However, there was no survival benefit for patients receiving chemotherapy. Conclusions: Primary renal LMS is exceedingly rare entity with distinct clinicopathological features and poor prognosis. Higher tumor grade and late stage may indicate poor prognosis. Complete tumor resection remains the first treatment choice and chemotherapy could be a palliative treatment choice for advanced patients.